Parenting Self-Efficacy in Immigrant Families—A Systematic Review - Boruszak-Kiziukiewicz, Joanna; Kmita, Grażyna (Frontiers in Psychology, 2020)
Introduction: Parenting self-efficacy (PSE) refers to parents’ belief in their ability to perform the parenting role successfully, and derives from Bandura’s concept of personal self-efficacy formulated within the social cognitive theory. PSE has been demonstrated to be a strong predictor of parenting functioning. At the same time, relatively less is known about its possible role in the situation of migration, when a family experiences acculturation stress in the process of adaptation to the new culture. Therefore, the aim of this systematic review was to summarize available data on the conceptualization, measurement and the role of parenting self-efficacy in the context of acculturation processes, and in various groups of immigrant parents. Methods: An extensive search of electronic databases was conducted in August 2018 and updated in February 2020 to identify peer-reviewed articles on parenting self -efficacy among immigrants. Eleven studies met pre-specified criteria for inclusion. Nine of the studies employed a quantitative design, whereas the remaining two studies used qualitative methods. In three of the quantitative studies, interventions/programs for immigrants were assessed. Results: Three different approaches to conceptualizing and measuring PSE were identified in the analyzed papers: domain-general, domain-specific, and narrow domain. Incongruent results were found with regards to the links between the strength of PSE and immigrants’ cultural orientation. Additionally, PSE was identified as a mediator between a stronger orientation towards the mainstream culture and more positive parenting practices, and more supportive parenting. The qualitative studies indicated that a reduction in PSE was typical for the initial period of immigration and might be a consequence of a forced orientation towards the standards of the receiving country, which was a consequence of the parents wanting to maintain close relations with their teenage children. Discussion: Overall, the theoretical and methodological quality of the reported studies varied and hence their findings have to be interpreted with caution. Our analysis clearly points to the usefulness of a multifaceted approach to PSE. Further research is needed to understand the mechanisms by which parental self-efficacy may exert a positive effect on the functioning of immigrant families.